Reduced-Order Observer-Based Consensus for Multi-Agent Systems With Time Delay and Event Trigger Strategy - Zhao, Daduan; Dong, Tao (IEEE access, 2017)
This paper investigates the reduced-order observer-based consensus problem of multi-agent system with time delay and event trigger strategy. First, a multi-step algorithm is presented to construct a reduced-order observer for each agent. Then, a novel push-based event-triggered control strategy, which based on the reduced-order observer and the relative outputs of neighboring agents is proposed. Under this control strategy, a sufficient condition for the consensus of multi-agent systems is obtained by using the integral inequality technique and matrix theory. Moreover, the estimation value of the output time delay is also obtained and the Zeno-behavior of triggering time sequences is excluded. Finally, two simulations about the multi-agent system are provided to illustrate the correctness of theoretical results.